THE HISTORICAL GEOGRAPHY OF THE KARABAKH REGION OF AZERBAIJAN IN THE POST-WAR YEARS (1946-1950) (Journal of history, 2024)
The article is devoted to the study of the historical geography of the Karabakh region of Azerbaijan in the post-war years (1946-1950) and is related to the impact of the Second World War on Azerbaijan, and Karabakh in particular. The reason for choosing this topic is the importance of Karabakh for Azerbaijan. The period of 1946-1950 has not been studied in the historical literature of Azerbaijan, especially from the historical and geographical side. The main direction is to show the changes taking place in 1946-1950, namely in the geography of the population and cultural geography. After the war, the population decreased sharply, which could have a bad effect on the future development of Karabakh, so much was done to change the situation and socio-cultural measures were taken to improve it.  A comparative method of historical geography was used in the article, which showed the dynamics and the results occurring during this period. The main result of the study is that the Second World War, despite the negative consequences (the population decline), opened a new path for further development in culture, education and many other spheres of the population of Karabakh.
Keywords: Azerbaijan, Karabakh, World War II, the historical geography, changes, the population, the education